Tobacco exposure and immunotherapy response in PD-L1 positive lung cancer patients. (December 2020) - Li, Janice J.N.; Karim, Khizar; Sung, Mike; Le, Lisa W.; Lau, Sally C.M.; Sacher, Adrian; Leighl, Natasha B.
Highlights: Smoking is associated with significantly better anti-PD-1 monotherapy response. Smoking history is a significant factor even after adjusting for PD-L1 TPS. Exploratory analysis demonstrated higher survival rates in smokers. Abstract: Background: Tobacco exposure contributes to over 80 % of lung cancer cases. Smoking is associated with programmed death-ligand 1 (PD-L1) tumor expression and better outcomes from anti-programmed cell death protein 1 (anti-PD-1) therapy in patients with advanced non-small cell lung cancer (NSCLC). PD-L1 tumor expression is now routinely used to predict benefit from anti-PD-1 therapy in patients with advanced NSCLC. In this study, we explored the impact of smoking status on patient outcomes with anti-PD-1 therapy in addition to PD-L1 tumor expression. Methods: A prospective real-world cohort of 268 patients with advanced NSCLC treated with anti-PD-1 monotherapy at the Princess Margaret Cancer Centre (PMCC) was used for this analysis. Logistic regression was performed to test factors associated with treatment response (RECIST v1.1), including PD-L1 tumour proportion score (TPS) and smoking status. Results: Overall response rates (ORR) to immunotherapy were significantly higher in current and former smokers than never smokers (36 % vs 26 % vs 14 %; p = 0.02). In patients with PD-L1 tumour proportion score (TPS) ≥50 %, current smokers continued to experience better ORR to anti-PD-1 therapy than never smokers (58 % vs 19 %; p = 0.03). Current smoking was associated with higher response even after adjusting for level of PD-L1 TPS expression (adjusted odds ratio 5.9, 95 % CI 1.6–25.0, p = 0.03). Exploratory analysis demonstrated higher 1-year survival rates in smokers compared to never smokers (p = 0.003). Conclusions: Smoking remains an important factor associated with response to anti-PD-1 monotherapy. Advanced NSCLC patients with positive PD-L1 expression are more likely to respond to anti-PD-1 monotherapy if they are current smokers compared to never smokers.